The untold story of Mariano Mendoza - Bean, Meosha; Mendoza, Mariano; M. V. B. Films Productions; Leomark Studios ([Los Angeles, California] : M.V.B. Films Productions, 2017)
Mariano Mendoza was born in Los Angeles, California. He is a U.S Navy Veteran. He is considered the Hispanic version of Debo/Van Damme Martial Artist and Thug. He is the first Hispanic Heavyweight Cage Fighter to fight in the W.V.C. in Brazil. --
Originally released as a motion picture in 2017.
Mariano Mendoza.
Cinematographers, Moesha Bean, Joshua Davila
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 30, 2020)
Keywords: Mendoza, Mariano; Martial artists -- California -- Los Angeles -- Biography; Veterans -- United States -- Biography; Hand-to-hand fighting -- California -- Los Angeles -- Biography; Documentary films; Nonfiction films; Biographical films; Internet videos; Streaming video